Considerations of prescribers and pharmacists for the use of non‐selective β‐blockers in asthma and COPD patients: An explorative study. Issue 2 (10th January 2018) - Kuipers, Esther; Wensing, Michel; De Smet, Peter A.G.M.; Teichert, Martina
Abstract: Rationale, aims, and objectives: Despite recommendations in prevailing guidelines to avoid the use of non‐selective (NS) β‐blockers in patients with asthma or COPD, on average, 10 patients per community pharmacy receive NS β‐blockers monthly. The aim of our study was to identify the reasons of prescribers and pharmacists to treat asthma and COPD patients with NS β‐blockers. Methods: Fifty‐three community pharmacists in the Netherlands selected patients with actual concurrent use of inhalation medication and NS β‐blockers. For at least 5 patients, each pharmacist screened all medication surveillance signals and actions taken at first dispensing. Each pharmacist selected 3 different initial prescribers for a short interview to explore their awareness of the co‐morbidity and reasons to apply NS β‐blockers. Results: Pharmacists identified 827 asthma/COPD patients with actual use of NS β‐blockers. From these, 153 NS β‐blocker prescribers were selected and interviewed (64 general practitioners, 45 ophthalmologists, 24 cardiologists, and 20 other prescribers). One hundred seven prescribers were aware of the drug‐disease interaction of the asthma or COPD co‐morbidity when initiating the NS β‐blocker, and 46 were not. From these, 40 prescribers did not consider the contraindication to be relevant. For 299 patients, medication surveillance signals and actions at first dispensing were retrieved. Patients used predominantly ocular timolol (39.8%), and the oral preparations propranolol (30.8%) and carvedilol (15.1%). In 154 cases, the pharmacy system generated a warning alert. Conclusions: A substantial number of prescribers was unaware of the co‐morbidity or did not regard NS β‐blockers contraindicated, despite prevailing clinical guidelines. Improvement programs should target prescribers' awareness and knowledge of NS β‐blockers in patients with asthma or COPD.